1988
DOI: 10.1172/jci113394
|View full text |Cite
|
Sign up to set email alerts
|

Complementary modes of action of tissue-type plasminogen activator and pro-urokinase by which their synergistic effect on clot lysis may be explained.

Abstract: Tissue plasminogen activator (t-PA) and/or pro-urokinase (pro-UK) induced lysis of standard '251-fibrin clots suspended in plasma was studied. Doses were kept below the concentration at which a nonspecific effect was seen, i.e., where fibrinogenolysis and major plasminogen consumption were observed. Small amounts of t-PA potentiated clot lysis by pro-UK by attenuating the lag phase characteristic of pro-UK, and causing a much earlier transition to the rapid phase of lysis. Similar promotion of the fibrinolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
85
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(96 citation statements)
references
References 21 publications
10
85
0
1
Order By: Relevance
“…When M5 (2 g/mL) was combined with a small amount (30 ng/mL) of tPA, which was insufficient to induce clot lysis by itself, the lag phase was reduced by half, as previously observed with similar combinations of tPA and proUK. 25 This has been ascribed to the creation of new (fragment E) plasminogen binding sites by tPA-induced lysis, which promote plasminogen activation by proUK and M5 (see Table 2). Therefore, fibrin-dependent plasminogen activation by M5 is similarly complementary to tPA (promoted by fragment D) as proUK 25 (data not shown).…”
Section: Clot Lysis In Human Plasma In Vitro By M5 or Prouk Over A Fimentioning
confidence: 99%
“…When M5 (2 g/mL) was combined with a small amount (30 ng/mL) of tPA, which was insufficient to induce clot lysis by itself, the lag phase was reduced by half, as previously observed with similar combinations of tPA and proUK. 25 This has been ascribed to the creation of new (fragment E) plasminogen binding sites by tPA-induced lysis, which promote plasminogen activation by proUK and M5 (see Table 2). Therefore, fibrin-dependent plasminogen activation by M5 is similarly complementary to tPA (promoted by fragment D) as proUK 25 (data not shown).…”
Section: Clot Lysis In Human Plasma In Vitro By M5 or Prouk Over A Fimentioning
confidence: 99%
“…These Lys binding sites are also important for the activation and regulation of plasminogen (Lijnen et al, 1980;Clemmensen, et al, 1981Clemmensen, et al, , 1986Pannell et al, 1988;Miles et al, 1991;Lenich et al, 1991). Specifically, the binding of ␣ 2 -antiplasmin to plasminogen have been shown to depend on Lys residues present in the COOHterminal region of ␣ 2 -antiplasmin (Sasaki et al, 1986;Hortin et al, 1988).…”
mentioning
confidence: 99%
“…In particular, it has been suggested that the binding of histidine-rich glycoprotein to the Lys binding sites of plasminogen may prevent the binding of plasminogen to fibrinogen and fibrin (Lijnen et al, 1980;Ichinose et al, 1984). It is similarly conceivable that a Lys-specific carboxypeptidase may interfere with the degradation of the fibrin clot by removing COOH-terminal Lys residues from fibrin (Pannell et al, 1988;Miles et al, 1991;Bajzar et al, 1995).…”
mentioning
confidence: 99%
“…Fibrinolysis induced by such low tPA concentrations can be explained by the complementary modes of action of tPA and proUK [15] and their ibrinolytic effect which when combined is synergistic [16]. Unlike tPA that is stored in the vessel wall, from where it initiates ibrinolysis, proUK is a is a normal constituent of blood, from where it continues ibrinolysis.…”
Section: How Thrombolysis Can Be Improved?mentioning
confidence: 99%
“…In view of the complementary properties of tPA and proUK and their complementary functions in ibrinolysis [15], a logical solution for improving thrombolysis is by using a combination of both plasminogen activators, as in physiological ibrinolysis.…”
Section: How Thrombolysis Can Be Improved?mentioning
confidence: 99%